Oil-water separation ultrafiltration membrane and preparation method and application thereof

By mixing polyvinylidene fluoride, pore-generating agent, phytic acid and zirconium salt and processing in a solidification bath of organosilane, an ultrafiltration membrane with good oil-water separation and anti-oil pollution performance is prepared. The problem of existing membranes being susceptible to oil contamination is achieved, and the reusable films and cost reduction are achieved.

CN118807473BActive Publication Date: 2025-02-07天津大学浙江研究院

Patent Information

Application Number
CN202411297474.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2025-02-07
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The existing oil-water separation membranes are susceptible to oil contamination when treating oil-containing wastewater, resulting in frequent replacement of membrane components, increasing operating costs.

Method used

Using a preparation method of oil-water separation ultrafiltration membrane, it is prepared by mixing polyvinylidene fluoride, pore-generating agent, phytic acid and zirconium salt and adding organic silane to coagulation bath to prepare good oil-water separation performance and resistance. Oil-contaminated membrane.

Benefits of technology

The membrane maintains good permeability flux and water permeability recovery rate during the oil-water separation process, has strong anti-oil pollution performance, can be reused, and reduces operating costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118807473B_ABST
    Figure CN118807473B_ABST
Patent Text Reader

Abstract

The present disclosure provides an oil-water separation ultrafiltration membrane and its preparation method and application, which belongs to the technical field of membrane material preparation. Preparation method: according to the mass of the casting liquid of 100wt%, 10~25wt% of polyvinylidene fluoride is mixed with 5~15wt% of porogen and 1~5wt% of phytic acid, and then 0.01~20wt% of zirconium salt is added, and the casting liquid is obtained after mixing and degassing; the casting liquid is coated on a flat plate to obtain a flat membrane; the flat membrane is placed in a coagulation bath for treatment; the coagulation bath includes an organic silane with a concentration of 0~100mM / L. Also disclosed is an oil-water separation ultrafiltration membrane prepared according to the above method and its application in an oil-water separation system. The oil-water separation ultrafiltration membrane prepared by the present disclosure has good oil-water separation performance, high water permeability recovery rate, strong anti-oil pollution performance, and has the advantages of reusability and low economic cost; the preparation method disclosed in the present disclosure is simple, the conditions are mild, and the scope of use is wide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of membrane material preparation, and in particular to an oil-water separation ultrafiltration membrane and a preparation method and application thereof. Background Art

[0002] Water shortage is becoming a global problem that needs to be solved urgently. Therefore, the recycling of freshwater resources is particularly important. Among them, it is urgent to increase the treatment of oily wastewater and improve the recovery rate of oily wastewater. Among the many oil-water separation technologies, membrane separation technology has been widely used in many fields such as food, medical care, energy and water treatment due to its simple operation, efficient separation, no phase change, energy saving and environmental friendliness. For oily wastewater with oil droplet diameters generally above 100nm, ultrafiltration membranes and microfiltration membranes with smaller pore sizes are generally used for treatment. However, membrane components are easily contaminated during the separation process, and frequent replacement of membrane components leads to high operating costs.

[0003] The mechanism of oil pollution on the membrane surface is spreading pollution. Due to the strong hydrophobicity of oil droplets and the hydrophobic interaction between oil droplets and membrane materials, the interfacial free energy of the oil film interface is much lower than that of the water film interface. According to Young's equation theory, the contact angle of oil droplets when spreading on the membrane surface is very small, that is, a small drop of oil can form a large area of ​​continuous oil film on the membrane surface. Driven by pressure, the oil film can enter the membrane pores and adhere to the pore walls to a certain extent. It is difficult to remove even under high-speed flushing, and only frequent backwashing can be performed. When emulsifiers are present, the dispersed particle size of oil droplets in water is greatly reduced, making it easier to enter the membrane pores, thereby expanding the pollution area and being extremely difficult to handle. Therefore, the preparation of separation membranes resistant to oil pollution is beneficial to ensure the oil-water separation performance while improving the service life of membrane components and reducing costs. Summary of the invention

[0004] The present disclosure provides an oil-water separation ultrafiltration membrane and a preparation method and application thereof, so as to at least solve the above technical problems existing in the prior art.

[0005] According to a first aspect of the present disclosure, a method for preparing an oil-water separation ultrafiltration membrane is provided, comprising the following steps:

[0006] S1: Based on the mass of the casting solution being 100wt%, 10-25wt% of polyvinylidene fluoride, 5-15wt% of a porogen and 1-5wt% of phytic acid are mixed, and then 0.01-20wt% of a zirconium salt is added, and the casting solution is obtained after mixing and degassing;

[0007] S2: coating the casting solution on a flat plate to obtain a flat plate membrane;

[0008] S3: placing the flat membrane in a coagulation bath to obtain the oil-water separation ultrafiltration membrane; the coagulation bath includes organosilane, and the concentration of the organosilane is 0-100 mM / L.

[0009] In one embodiment, in step S1, the polyvinylidene fluoride is first dissolved in a 40-80wt% solvent, and then mixed with the porogen and the phytic acid; the solvent is selected from at least one of dimethylacetamide, dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone.

[0010] In one embodiment, the porogen is selected from at least one of polyvinyl pyrrolidone, polyethylene glycol, and polyvinyl alcohol.

[0011] In one embodiment, the zirconium salt is selected from an organic zirconium salt or an inorganic zirconium salt.

[0012] In one embodiment, the zirconium salt is selected from at least one of tetrabutyl zirconate, zirconium isopropoxide, tetrabenzyl zirconium, zirconium acetate, zirconium chloride, zirconium nitrate, zirconium sulfate, and zirconium n-propoxide.

[0013] In one embodiment, after adding the zirconium salt in step S1, stirring is performed in an oil bath at 60-80° C. for 6-12 hours until the solution becomes clear and transparent, and the mixture is allowed to stand for 12-24 hours to degas and mature, thereby obtaining the casting solution.

[0014] In one possible implementation, the flat plate in step S2 is not specifically limited, and may be, for example, a glass plate.

[0015] In one possible implementation manner, after the flat membrane is prepared in step S2, it is placed in air for 10 to 30 seconds.

[0016] In one embodiment, the temperature of the coagulation bath is 25-28°C.

[0017] In a preferred embodiment, the temperature of the coagulation bath is 25°C.

[0018] In one embodiment, in step S3, the flat membrane is placed in the coagulation bath for a treatment time of 30 to 60 seconds.

[0019] In one embodiment, the organosilane is at least one selected from 3-aminopropyltriethoxysilane, polydimethylsiloxane, tert-butyldimethylchlorosilane, and perfluorododecyltrichlorosilane.

[0020] According to a second aspect of the present disclosure, there is provided an oil-water separation ultrafiltration membrane prepared according to the above preparation method.

[0021] According to a third aspect of the present disclosure, there is provided application of the above-mentioned oil-water separation ultrafiltration membrane in an oil-water separation system.

[0022] According to an implementable embodiment of the present disclosure, at least the following beneficial effects are achieved:

[0023] The oil-water separation ultrafiltration membrane prepared by the present disclosure has good oil-water separation performance, the permeation flux is stable at about 200 when filtering oil, the water permeability recovery rate is high, the oil pollution resistance performance is strong, and it has the advantages of reusability and low economic cost (while the permeation flux of commercial membranes can drop to below 100 when filtering oil; and the permeation flux of some commercial membranes drops after filtration and cannot be recovered). The preparation method disclosed by the present disclosure is simple, the preparation conditions are mild, the application range is wide, and it is easy to scale up and promote.

[0024] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:

[0026] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.

[0027] Figure 1 A schematic diagram of the process for preparing an ultrafiltration membrane for oil-water separation disclosed in the present invention is shown;

[0028] Figure 2 The oil-water separation performance test diagram of the 0-zirconium silicon oil-water separation ultrafiltration membrane in Example 1 of the present disclosure is shown;

[0029] Figure 3 The oil-water separation performance test diagram of the 0.5-zirconium silicon oil-water separation ultrafiltration membrane in Example 2 of the present disclosure is shown;

[0030] Figure 4 The oil-water separation performance test diagram of the 1.0-zirconium silicon oil-water separation ultrafiltration membrane in Example 3 of the present disclosure is shown;

[0031] Figure 5 The oil-water separation performance test diagram of the 1.5-zirconium-silicon oil-water separation ultrafiltration membrane in Example 4 of the present disclosure is shown;

[0032] Figure 6 A scanning electron microscope image of the inner surface of the 2.0-zirconium-silicone oil-water separation ultrafiltration membrane in Example 5 of the present disclosure is shown;

[0033] Figure 7 A scanning electron microscope image of the outer surface of the 2.0-zirconium silicon oil-water separation ultrafiltration membrane in Example 5 of the present disclosure is shown;

[0034] Figure 8 A scanning electron microscope image of a cross section of a 2.0-zirconium-silicon oil-water separation ultrafiltration membrane in Example 5 of the present disclosure is shown;

[0035] Fig. 9 The oil-water separation performance test diagram of the 2.0-zirconium silicon oil-water separation ultrafiltration membrane in Example 5 of the present disclosure is shown.

[0036] Reference numerals:

[0037] 1-polyvinylidene fluoride; 2-porogen; 3-phytic acid; 4-solvent; 5-zirconium salt; 6-casting solution; 7-flat membrane;

[0038] 8-Coagulation bath; 9-Ultrafiltration membrane for oil-water separation. DETAILED DESCRIPTION

[0039] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0040] The present invention provides a method for preparing an ultrafiltration membrane for oil-water separation, and the schematic diagram of the process is shown in Figure 1 , specifically including the following steps:

[0041] S1: Based on the mass of the casting liquid being 100wt%, 10-25wt% of polyvinylidene fluoride 1 is first dissolved in 40-80wt% of solvent 4, and then mixed with 5-15wt% of porogen 2 and 1-5wt% of phytic acid 3, and then 0.01-20wt% of zirconium salt 5 is added, and the casting liquid 6 is obtained after mixing and degassing;

[0042] S2: coating the casting solution 6 on a flat plate to obtain a flat plate membrane 7;

[0043] S3: placing the flat membrane 7 in a coagulation bath 8 for treatment to obtain an oil-water separation ultrafiltration membrane 9; the coagulation bath 8 includes organic silane, and the concentration of the organic silane is 0-100 mM / L.

[0044] There is no particular limitation on the sources of all raw materials in the present disclosure and the following examples, and any raw materials may be commercially available.

[0045] The detection method of water permeation flux in the following embodiments is as follows:

[0046] The test system of Hangzhou Saifei Membrane Separation Technology Co., Ltd. was used to test the permeability of the membrane to water and water-in-oil emulsion. The test system consists of pumps, membrane tanks, pipelines, regulating valves, pressure and flow detectors and other components. The test pressure is 0.5 bar and the test temperature is 25±0.5℃.

[0047] The permeability of water and oil-in-water emulsions was calculated as follows: J = V / [A × Δt × Δp];

[0048] Where V is the permeate volume (L), A is the effective membrane area (m 2 ), Δt is the permeation time (s), Δp is the test pressure (bar), J is the permeability of the membrane (L m -2 h -1 bar -1 Specifically, the initial permeability of water is recorded as J w1 , the initial permeability of the oil-in-water emulsion is recorded as J o1 , the water permeability of the membrane after washing is recorded as J w2 .

[0049] Example 1

[0050] In this embodiment, a 0-zirconium-silicone oil-water separation ultrafiltration membrane is prepared, and the specific process is as follows:

[0051] (1) Based on the mass of the casting liquid being 100wt%, 17wt% of polyvinylidene fluoride powder was dissolved in 76.95wt% of dimethylacetamide, 5wt% of polyvinyl pyrrolidone and 1wt% of phytic acid were added, and after stirring into a uniform solution, 0.05wt% of ZrCl4 was added, and the mixture was stirred at 60°C in an oil bath for 8h until the mixed solution became clear and transparent, and the mixed solution was allowed to stand for 12h to degas and mature, thereby obtaining a casting liquid;

[0052] (2) Use a scraper to evenly coat the casting solution on a clean glass plate to obtain a flat film, and place the flat film in air for 30 seconds;

[0053] (3) The flat membrane in step (2) was immersed in a deionized water coagulation bath at 25° C. for 60 seconds to obtain a 0-zirconium-silicone oil-water separation ultrafiltration membrane.

[0054] The oil-water separation performance of 0-zirconium-silicon oil-water separation ultrafiltration membrane was tested, and the results are as follows: Figure 2 shown. Figure 2 The water permeability of the membrane (J w1 ) is 1301 L m -2 h -1 bar -1 , permeability of oil-in-water emulsions (J o1 ) is 210 L m -2 h -1bar -1 The tested membrane was first rinsed with ultrapure water and then with anhydrous ethanol. The water permeability (J w2 ) is 1061 L m -2 h -1 bar -1 .

[0055] Example 2

[0056] In this example, a 0.5-zirconium-silicone oil-water separation ultrafiltration membrane was prepared, and the specific process was as follows:

[0057] (1) Based on the mass of the casting liquid being 100wt%, 17wt% of polyvinylidene fluoride powder was dissolved in 76.95wt% of dimethylacetamide, 5wt% of polyvinyl pyrrolidone and 1wt% of phytic acid were added, and after stirring into a uniform solution, 0.05wt% of ZrCl4 was added, and the mixture was stirred at 60°C in an oil bath for 8h until the mixed solution became clear and transparent, and the mixed solution was allowed to stand for 24h to degas and mature, thereby obtaining a casting liquid;

[0058] (2) Use a scraper to evenly coat the casting solution on a clean glass plate to obtain a flat film, and place the flat film in air for 30 seconds;

[0059] (3) The flat membrane prepared in step (2) was immersed in a coagulation bath at 25° C. (the coagulation bath contained 0.5 mM / L 3-aminopropyltriethoxysilane (APTES)) for 60 s to prepare a 0.5-zirconium silicate oil-water separation ultrafiltration membrane.

[0060] The oil-water separation performance of 0.5-zirconium-silicon oil-water separation ultrafiltration membrane was tested. Figure 3 shown. Figure 3 The water permeability of the membrane (J w1 ) is 1014 L m -2 h -1 bar -1 , permeability of oil-in-water emulsions (J o1 ) is 183 L m -2 h - 1 bar -1 The tested membrane was first rinsed with ultrapure water and then with anhydrous ethanol. The water permeability (J w2 ) is 688 Lm -2 h -1 bar -1 .

[0061] Example 3

[0062] In this example, a 1.0-zirconium-silicone oil-water separation ultrafiltration membrane was prepared, and the specific process was as follows:

[0063] (1) Based on the mass of the casting liquid being 100wt%, 17wt% of polyvinylidene fluoride powder was dissolved in 76.95wt% of dimethylacetamide, 5wt% of polyvinyl pyrrolidone and 1wt% of phytic acid were added, and after stirring into a uniform solution, 0.05wt% of ZrCl4 was added, and the mixture was stirred at 60°C in an oil bath for 8h until the mixed solution became clear and transparent, and the mixed solution was allowed to stand for 24h to degas and mature, thereby obtaining a casting liquid;

[0064] (2) Use a scraper to evenly coat the casting solution on a clean glass plate to obtain a flat film, and place the flat film in air for 30 seconds;

[0065] (3) The flat membrane prepared in step (2) was immersed in a coagulation bath at 25° C. (the coagulation bath contained 1.0 mM / L 3-aminopropyltriethoxysilane) for 60 s to prepare a 1.0-zirconium silicate oil-water separation ultrafiltration membrane.

[0066] The oil-water separation performance of 1.0-zirconium-silicon oil-water separation ultrafiltration membrane was tested, and the results are as follows Figure 4 shown. Figure 4 The water permeability of the membrane (J w1 ) is 1616 L m -2 h -1 bar -1 , permeability of oil-in-water emulsions (J o1 ) is 219 L m -2 h - 1 bar -1 The tested membrane was first rinsed with ultrapure water and then with anhydrous ethanol. The water permeability (J w2 ) is 751 Lm -2 h -1 bar -1 .

[0067] Example 4

[0068] In this example, a 1.5-zirconium-silicone oil-water separation ultrafiltration membrane was prepared, and the specific process was as follows:

[0069] (1) Based on the mass of the casting liquid being 100wt%, 17wt% of polyvinylidene fluoride powder was dissolved in 76.95wt% of dimethylacetamide, 5wt% of polyvinyl pyrrolidone and 1wt% of phytic acid were added, and after stirring into a uniform solution, 0.05wt% of ZrCl4 was added, and the mixture was stirred at 60°C in an oil bath for 8h until the mixed solution became clear and transparent, and the mixed solution was allowed to stand for 24h to degas and mature, thereby obtaining a casting liquid;

[0070] (2) Use a scraper to evenly coat the casting solution on a clean glass plate to obtain a flat film, and place the flat film in air for 30 seconds;

[0071] (3) The flat membrane prepared in step (2) was immersed in a coagulation bath at 25° C. (the coagulation bath contained 1.5 mM / L 3-aminopropyltriethoxysilane) for 60 s to prepare a 1.5-zirconium silicate oil-water separation ultrafiltration membrane.

[0072] The oil-water separation performance of 1.5-zirconium-silicon oil-water separation ultrafiltration membrane was tested. Figure 5 shown. Figure 5 The water permeability of the membrane (J w1 ) is 2046 L m -2 h -1 bar -1 , permeability of oil-in-water emulsions (J o1 ) is 190 L m -2 h - 1 bar -1 The tested membrane was first rinsed with ultrapure water and then with anhydrous ethanol. The water permeability (J w2 ) is 1545L m -2 h -1 bar -1 .

[0073] Example 5

[0074] In this example, a 2.0-zirconium-silicone oil-water separation ultrafiltration membrane was prepared, and the specific process was as follows:

[0075] (1) Based on the mass of the casting liquid being 100wt%, 17wt% of polyvinylidene fluoride powder was dissolved in 76.95wt% of dimethylacetamide, 5wt% of polyvinyl pyrrolidone and 1wt% of phytic acid were added, and after stirring into a uniform solution, 0.05wt% of ZrCl4 was added, and the mixture was stirred at 60°C in an oil bath for 8h until the mixed solution became clear and transparent, and the mixed solution was allowed to stand for 24h to degas and mature, thereby obtaining a casting liquid;

[0076] (2) Use a scraper to evenly coat the casting solution on a clean glass plate to obtain a flat film, and place the flat film in air for 30 seconds;

[0077] (3) The flat membrane prepared in step (2) was immersed in a coagulation bath at 25° C. (the coagulation bath contained 2.0 mM / L 3-aminopropyltriethoxysilane) for 60 s to obtain a 2.0-zirconium silicate oil-water separation ultrafiltration membrane.

[0078] The structure of 2.0-zirconium-silicon oil-water separation ultrafiltration membrane was observed by scanning electron microscopy. Figure 6 , Figure 7 , Figure 8 shown. Figure 6 , Figure 7 , Figure 8 It shows that the structure of the inner surface of the membrane is denser and the pore size is smaller; the outer surface has larger pores, and the cross-sectional view also shows the corresponding structure. The above structure enables the membrane to separate oil and water so that oil droplets can only enter the larger pores on the outer surface, but not the tiny pores on the inner surface. This makes it easier to rinse the oil off the membrane for reuse, thereby increasing the service life of the membrane assembly and reducing costs. In addition, the above structure enables the membrane to have good oil-water separation performance, a high water permeability recovery rate, and strong resistance to oil pollution. The oil-water separation performance of the 2.0-zirconium-silicone oil-water separation ultrafiltration membrane was tested, and the results are as follows: Fig. 9 shown. Fig. 9 The water permeability of the membrane (J w1 ) is 1940 L m -2 h - 1 bar -1 , permeability of oil-in-water emulsions (J o1 ) is 229 L m -2 h -1 bar -1 The membrane was directly used for water permeability test again after the test. The results showed that the water permeability (J w2 ) is 534 L m -2 h -1 bar -1 .

[0079] The statistical results of the oil-water separation performance test of the oil-water separation ultrafiltration membranes prepared in the above Examples 1 to 5 are shown in Table 1.

[0080] Table 1

[0081]

[0082] It can be seen that the zirconium-silicon oil-water separation ultrafiltration membrane prepared in the present invention has good oil-water separation performance, high water permeability recovery rate, strong anti-pollution performance, and has the advantages of reusability and low economic cost.

[0083] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solution of this disclosure can be achieved, and this document is not limited here.

[0084] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0085] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A method for preparing an ultrafiltration membrane for oil-water separation, characterized in that: The following steps are involved: S1: Based on the mass of the casting solution being 100wt%, 10-25wt% of polyvinylidene fluoride, 5-15wt% of a porogen and 1-5wt% of phytic acid are mixed, and then 0.01-20wt% of a zirconium salt is added, and the casting solution is obtained after mixing and degassing; S2: coating the casting solution on a flat plate to obtain a flat plate membrane; S3: placing the flat membrane in a coagulation bath to obtain the oil-water separation ultrafiltration membrane; the coagulation bath comprises an organosilane, the concentration of the organosilane is 1.0-2.0 mM; the temperature of the coagulation bath is 25-28° C.; the organosilane is selected from at least one of 3-aminopropyltriethoxysilane, polydimethylsiloxane, tert-butyldimethylchlorosilane, and perfluorododecyltrichlorosilane; Step S1: first dissolving the polyvinylidene fluoride in 40-80wt% of a solvent, and then mixing it with the porogen and the phytic acid; In step S3, the flat membrane is placed in the coagulation bath for a treatment time of 30 to 60 seconds.

2. The preparation method according to claim 1, characterized in that: The solvent is selected from at least one of dimethylacetamide, dimethylformamide, dimethyl sulfoxide, and N-methylpyrrolidone; The porogen is selected from at least one of polyvinyl pyrrolidone, polyethylene glycol and polyvinyl alcohol.

3. The preparation method according to claim 1, characterized in that: The zirconium salt is selected from at least one of tetrabutyl zirconate, zirconium isopropoxide, tetrabenzyl zirconium, zirconium acetate, zirconium chloride, zirconium nitrate, zirconium sulfate and zirconium n-propoxide.

4. The preparation method according to claim 1, characterized in that: Step S1: After adding the zirconium salt, stir in an oil bath at 60-80° C. for 6-12 hours until the solution becomes clear and transparent, and let stand for 12-24 hours to degas and mature the mixed solution to obtain the casting solution.

5. The preparation method according to claim 1, characterized in that: After the flat membrane is obtained in step S2, it is placed in air for 10 to 30 seconds.

6. An oil-water separation ultrafiltration membrane prepared according to the preparation method according to any one of claims 1 to 5.

7. Use of the oil-water separation ultrafiltration membrane according to claim 6 in an oil-water separation system.

Citation Information

Patent Citations

  • Preparation method of anti-pollution polymer-inorganic hybrid membrane

    CN107349799A

  • Janus organic porous material as well as preparation method and application thereof

    CN112796154A

Cited By

  • Sewage solid-liquid separation treatment method based on porous medium

    CN120757252A